An outdoor antenna metrology facility for candidate Square Kilometre Array antennas - Jiwani, A.; Flexman, J.; Padhi, S.; De Vaate, J.; Hall, Peter (2011)
The Square Kilometre Array (SKA) will be the largest radio telescope ever built operating at multiple frequency bands. The lowest band, SKA-low, covers 70 - 450 MHz and consists of sparse aperture arrays. The International Centre for Radio Astronomy Research (ICRAR) is investigating conical spirals as one candidate antenna for SKA-low. These large (~1 m) low frequency antennas are characterized using a quick and efficient procedure called the 'car-park' pattern measurement method. To verify the viability of the method, the characteristics of scaled conical spiral antenna prototypes, measured in both the car-park and an anechoic chamber, are compared in this paper. Initial indications confirm the reliability of the car-park measurement method and, by extrapolation, its suitability measuring full-sized antennas.